2012
DOI: 10.1210/en.2012-1303
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Basis for Glucocorticoid Induction of the Krüppel-Like Factor 9 Gene in Hippocampal Neurons

Abstract: Stress has complex effects on hippocampal structure and function, which consequently affects learning and memory. These effects are mediated in part by circulating glucocorticoids (GC) acting via the intracellular GC receptor (GR) and mineralocorticoid receptor (MR). Here, we investigated GC regulation of Krüppel-like factor 9 (KLF9), a transcription factor implicated in neuronal development and plasticity. Injection of corticosterone (CORT) in postnatal d 6 and 30 mice increased Klf9 mRNA and heteronuclear RN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
43
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(48 citation statements)
references
References 45 publications
3
43
0
Order By: Relevance
“…2 and 3). These findings are supported by studies that have demonstrated that glucocorticoid receptor directly regulates several members of the KLF family (41,42). We also found that KLF13 is a direct target of GR and its regulation involves binding of activated glucocorticoid receptors to a conserved and functional GRE within intron 1 of the Klf13 gene (Figs.…”
Section: Discussionsupporting
confidence: 87%
“…2 and 3). These findings are supported by studies that have demonstrated that glucocorticoid receptor directly regulates several members of the KLF family (41,42). We also found that KLF13 is a direct target of GR and its regulation involves binding of activated glucocorticoid receptors to a conserved and functional GRE within intron 1 of the Klf13 gene (Figs.…”
Section: Discussionsupporting
confidence: 87%
“…As mentioned earlier, KLF9 is implicated in neuronal development, and recent studies have also determined that KLF9 regulates neuronal plasticity by mediating the stress-induced effects of glucocorticoids in hippocampal neurons (Bagamasbad et al, 2012;Bonett et al, 2009). In addition, thyroid hormone induced oligodendrocyte differentiation and myelin regeneration are regulated by KLF9, which has direct implications in demyelinating disorders such as multiple sclerosis (Dugas et al, 2012).…”
Section: Klfs In Neuronal Disordersmentioning
confidence: 82%
“…For instance, in silico analysis of transcription factor binding sites presented specificity protein 1 (Sp1) and Krüppel-like factor 9 (Klf9) sites within the DNA sequence of area A. The Klf9 gene contains glucocorticoid response elements (GREs), and expression is induced in response to elevated corticosterone levels (29), which are known to occur after FS (30). Thus, the SAM and FS-induced increases in CpG methylation in this region of the Egr-1 gene may have disrupted Klf9-mediated (and possibly Sp1-mediated) transcriptional activation, but confirmation of this postulate requires further investigation.…”
Section: Discussionmentioning
confidence: 99%